PHYSIOLOGICAL FOUNDATIONS OF PHOTOPERIODISM AND PHYTOCHROME SYSTEM IN PLANTS - Muroddinova, Farida Rakhmatboy qizi (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the physiological foundations of photoperiodism and the phytochrome system, detailing their mechanisms and assessing their ecological and agricultural implications. Method: The research examines the role of the phytochrome pigment system, which senses red and far-red light, and its mediation of changes in day length to regulate plant physiological processes like flowering, dormancy, and seed germination. Result: The research demonstrates that phytochrome, through its Pr and Pfr forms, governs gene expression and hormone production to regulate flowering and growth. It shows that short-day and long-day plants exhibit distinct phytochrome responses, while day-neutral plants rely on alternate factors. Novelty: By connecting molecular mechanisms of phytochrome signaling with real-world plant behavior and environmental adaptation, the paper offers a comprehensive synthesis linking basic plant science with agronomic applications. Understanding these systems allows for better crop scheduling, yield optimization in controlled environments, and adaptation of plant species to new climates through light management. This knowledge is crucial for sustainable agriculture and the development of high-yielding, climate-resilient plant varieties.